Prediagnostic Body Weight and Survival in High Grade Glioma - Siegel, Erin M. (2013)
INTRODUCTION: Greater adiposity has been linked to an increased risk and/or poorer survival in a variety of cancers. We examined whether prediagnostic body weight 1–5 years prior to diagnosis is associated with survival in patients with high grade glioma. METHODS: The analysis was based on a series of patients with high-grade glioma (N=853) enrolled in a US-based multicenter case-control study. Subjects reported height and weight 1–5 years prior to interview and at age 21. BMI was categorized according to WHO criteria as underweight (BMI<18.5kg/m(2)), normal weight (BMI 18.5–24.9kg/m(2)), overweight (BMI 25–29.9kg/m(2)) and obese (BMI≥30kg/m(2)). Proportional hazards regression was used to estimate hazard ratios (HR) and 95% confidence intervals (CIs) for glioma-related death according to body mass index (BMI, kg/m(2)). RESULTS: Overall survival was reduced among patients underweight (median survival: 12.0 months) or obese (median: 13.6 months) when compared to patients of normal weight (median: 17.5 months) prior to glioma diagnosis (p=0.004). In a multivariate model controlling for other prognostic factors, an excess mortality was observed in patients reporting obese body weights 1–5 years prior to study interview when compared to patients with a normal BMI (HR=1.32; 95% CI:1.04–1.68). Consistent patterns of association with excess body weight were observed in men and women, and all findings were similar regardless of treatment for glioma. A lower than optimal body weight was associated with a nonsignificant excess mortality in multivariate analysis. CONCLUSIONS: Premorbid obesity was significantly associated with a poor patient outcome independent of treatment and established prognostic factors. Excess body weight may be an adverse prognostic factor in glioma, a relationship observed across a spectrum of cancer types. The current findings linking prediagnostic body weight with mortality in high-grade glioma warrant further research.